Analisis Neraca Air Pada Pulau Bengkalis - Delta, Novia; Fauzi, Manyuk; Hendri, Andy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The increasing number of population and the development of Bengkalis Island area that happens every year, give effect to the improvement of water requirement. It causes problem of imbalance between the availability and requirement of water. Therefore, water balance analysis in Bengkalis Island become an interesting thing to be studied. The water availability can be calculated using the Mock method or Nreca method. Water availability is calculated under several conditions, such as: dry (Q80%), normal (Qaverage) and wet (Q20%). While the water requirement is calculated based on domestic water requirement and non-domestic requirement. The water balance analysis calculated based on dry conditions (Q80%) can be concluded with a water surplus, only at the time of August period 2 which experienced deficit of 1,481 m3/sec . As for wet conditions (Q20%) and normal conditions (Qaverage) will be surplus for the next 20 years. Keywords: water availability, water requirement, water balance, Mock method, Nreca method